Microsoft Exchange server 2007 with SP1 Tony Redmond's guide to successful implementation - Redmond, Tony, 1959- (Burlington, MA : Elsevier/Digital Press, 2008)
Exchange 2007 represents the biggest advance in the history of Microsoft Exchange Server technology. Given Exchange's leap to x64 architecture and its wide array of new features, it isn't surprising that the SP1 release of 2007 would be particularly robust in terms of hotfixes, security enhancements and additional functionality. Tony Redmond's upgraded edition of his popular Microsoft Exchange Server 2007 bible features extensive coverage of the significant changes and additions offered with SP1. Every chapter has been updated, with particular focus on the most pivotal aspects of SP1, including: *install enabling on Windows Server 2008 *IVp6 support *Unified Messaging inclusion *EMC enhancements *Client Access Improvements for Outlook Web Access and Activesync *New user interfaces for POP3 and IMAP4 *System resource monitoring and message routing improvements *New features for the mailbox server role *.pst file data management improvements *new high-availability features *optimization for mobile access *and much more! *Complete coverage of all the updates in SP1 ensure admins skip the initial 2007 release's bugs and upgrade with ease *Written by HP Services CTO Tony Redmond, the world's most trusted author of Exchange books for over a decade *250+ pages of updates throughout, including totally new sections on Windows 2008 compatibility, Microsoft Yona, Windows Mobile 6 and 6.1 devices, Apple iPhone, and more!
Introduction -- Exchange and Windows -- Basics of management -- PowerShell -- The Store -- Transport and Routing -- Clients -- Managing Users -- Hardware -- Useful things to know.
Includes index.
Keywords: Microsoft Exchange server; Client/server computing; Electronic mail systems; Electronic books